2020
DOI: 10.1007/s41030-020-00124-7
|View full text |Cite|
|
Sign up to set email alerts
|

Physiologically Based Pharmacokinetic Modeling of CFTR Modulation in People with Cystic Fibrosis Transitioning from Mono or Dual Regimens to Triple-Combination Elexacaftor/Tezacaftor/Ivacaftor

Abstract: Introduction: The triple-combination (TC) cystic fibrosis transmembrane conductance regulator (CFTR) modulator regimen elexacaftor, tezacaftor, and ivacaftor was shown to be safe and efficacious in phase 3 trials of people with cystic fibrosis (pwCF) C 12 years of age with C 1 F508del-CFTR allele. Here, a simulation study predicted ivacaftor, tezacaftor, and elexacaftor exposures and impacts on CFTR modulation following transition from ivacaftor [a cytochrome P450 3A (CYP3A) substrate], lumacaftor (a CYP3A ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…It was constructed based on available physicochemical properties and clinical data from published PK studies. 11 , 14 , 15 , 16 , 17 The in vitro studies and clinical DDI data suggest that ivacaftor is predominantly eliminated through CYP3A4‐mediated hepatic metabolism. 13 Therefore, the excretion was set to enzyme kinetics to quantify its metabolism by CYP3A.…”
Section: Methodsmentioning
confidence: 99%
“…It was constructed based on available physicochemical properties and clinical data from published PK studies. 11 , 14 , 15 , 16 , 17 The in vitro studies and clinical DDI data suggest that ivacaftor is predominantly eliminated through CYP3A4‐mediated hepatic metabolism. 13 Therefore, the excretion was set to enzyme kinetics to quantify its metabolism by CYP3A.…”
Section: Methodsmentioning
confidence: 99%
“…For the PBPK model of ivacaftor, in the absence of an in vitro estimate, clinical interaction data with strong modulators of CYP3A4 were used to assign fmCYP3A4. First, we predicted DDI with ketoconazole by varying the fmCYP3A4 value of ivacaftor from 95% to 100% ( Figure S1A ), since it has been reported that the fractional metabolism of ivacaftor assigned to CYP3A4 is greater than 95%(17). An fmCYP3A4 of 98 % predicted the AUC ratio (GMR 6.95) of ivacaftor within the bioequivalence limit (80-125%) of the observed AUC ratio (GMR 8.45).…”
Section: Resultsmentioning
confidence: 99%
“…al. published a ETI PBPK model to evaluate exposures during the transition from mono or dual combination of CFTR modulators to ETI(17). We extended the models by refining the ivacaftor model and further validating the ETI PBPK-DDI model with published clinical DDI data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations